Medial and Lateral Posterior Tibial Slope in the Skeletally Immature: A Cadaveric Study. Issue 4 (4th April 2022) - Anchustegui, Nicolas; Grimm, Nathan L.; Milbrandt, Todd A.; Rustad, Audrey; Shea, Cooper; Troyer, Stockton; Dingel, Aleksei B.; Ganley, Theodore J.; Fabricant, Peter D.; Shea, Kevin G.
Background: An increased posterior tibial slope (PTS) results in greater force on the anterior cruciate ligament (ACL) and is a risk factor for ACL injuries. Biomechanical studies have suggested that a reduction in the PTS angle may lower the risk of ACL injuries. However, the majority of these investigations have been in the adult population. Purpose: To assess the mean medial and lateral PTS on pediatric cadaveric specimens without known knee injuries. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 39 pediatric knee specimens with computed tomography scans were analyzed. Specimens analyzed were between the ages of 2 and 12 years. The PTS of each specimen was measured on sagittal computed tomography slices at 2 locations for the medial and lateral angles. The measurements were plotted graphically by age to account for the variability in development within age groups. The anterior medial and lateral tibial plateau widths were measured. The distance between the top of the tibial plateau and the physis was measured. The independent-samples t test and analysis of variance were used to analyze the measurements. Results: The mean PTS angle for the medial and lateral tibial plateaus was 5.53° ± 4.17° and 5.95° ± 3.96°, respectively. The difference between the PTS angles of the medial and lateral tibial plateaus was not statistically significant ( P > .05). When plotted graphically by age, no trend between age and PTS was identified. Conclusion: This data set offers values for the PTS in skeletally immature specimens without a history of ACL injury and suggests that age may not be an accurate predictive factor for PTS.